Perencanaan Sarana Prasarana Pendidikan - Niken Ristianah (Intizam, Jurnal Manajemen Pendidikan Islam, 2018)
Educational facilities and infrastructure planning is the initial stage and becomes the basic basis in the process of procurement, use, maintenance and elimination of infrastructure facilities in educational institutions. But not infrequently the existing planning in the school is not carried out optimally so that the management of educational facilities does not get effective and efficient results. To get maximum results, the education community should understand what infrastructure facilities are planning, the benefits and objectives, principles, conditions, stages and classification of educational facilities. Good planning that can answer 5W 1H in the design of infrastructure programs that will be implemented so that its existence can help achieve goals and avoid unwanted errors and failures. Where infrastructure planning is an intellectual program, a needs analysis is carried out in a comprehensive, realistic, clear and detailed manner. Educational facilities and infrastructure planning is classified into three, first, based on the depletion or not, which is divided into two wearable and durable parts. Both are based on moving or not moving, the three facilities and infrastructure related to the teaching and learning process. DS PAUD schools have implemented planning in managing educational infrastructure. The step of analyzing needs by accommodating all proposals of the school community and designing needs in accordance with the classification so that they can be integrated with the infrastructure that has been available before and determine how to procure it. The next step is budget analysis. The needs that have been arranged are adjusted to the budget so that the party responsible for infrastructure can determine the priority scale in the procurement of infrastructure